Application of microprobe soft X-ray fluorescence and absorption spectroscopic analyses to characterize the buried multi-layered micro-structure. (29th May 2020) - Oura, Masaki; Ishihara, Tomoko; Yamaguchi, Akinobu
Abstract: We have applied a recently developed scanning soft X-ray (SX) spectromicroscope to characterize the buried multi-layered micro-structure by means of microprobe X-ray fluorescence ( μ XRF) analyses. We could successfully visualize single element maps of O and Fe contained in a buried 500 μ m square test-pattern made of SiO2 and Ni81 Fe19 (permalloy) beneath 30 nm thick Au coating. For their chemical-state analyses, we measured O K α and Fe L α X-rays emitted from the buried micro-structure using a SX microprobe to explore the X-ray absorption spectroscopy spectra of O and Fe contained in a local area by partial fluorescence yield spectroscopy.